Hubungan Jenjang Pendidikan Ibu dengan Kebiasaan Memberikan MP-ASI - Endang Maryani; Intin Ananingsih (Journal of Ners and Midwifery, 2014)
The process of giving of MP-ASI is one diet that formed by person's eating habits and culture. In the process of giving MP-ASI, education level takes an important role on it. Method: The research design was correlational design. The research sample was 20 mothers in Posyandu Dayu Village, Nglegok Subdistric, Blitar. It was choosen using total sampling. The data was collected using questionnaire. The data was analysed using Spearman Rank Test. Result : The results showed by Spearman Rank correlation (Rho) that theÂ  p value = 0,006. Discussion : Based on the results of the research it could be expected that mothers with 6-9 months baby more active to increase their knowledge in MP-ASI from electronic and mass media so that they could increase their capability of providing MP-ASI in the baby 6-9 months.